2013
DOI: 10.1097/sla.0b013e3182895bb0
|View full text |Cite
|
Sign up to set email alerts
|

Operative Management of Rib Fractures in the Setting of Flail Chest

Abstract: Background Flail chest (FC) results in paradoxical chest wall movement, altered respiratory mechanics, and frequently respiratory failure. Despite advances in ventilatory management, FC remains associated with significant morbidity and mortality. Operative fixation of the flail segment has been advocated as an adjunct to supportive care, but no definitive clinical trial exists to delineate the role of surgery. Objective To perform a systematic review and meta-analysis of studies comparing operative to nonope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
1
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(172 citation statements)
references
References 45 publications
12
150
1
9
Order By: Relevance
“…If there is a dislocation of the upper hemithorax with marked dislocation, an operative care should be considered, for example following the procedure shown in this manuscript. The overwhelming majority of the described collective showed very good postoperative results and a high quality of life (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…If there is a dislocation of the upper hemithorax with marked dislocation, an operative care should be considered, for example following the procedure shown in this manuscript. The overwhelming majority of the described collective showed very good postoperative results and a high quality of life (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…They occur in more than 16 % out of all polytrauma patients with an ISS of more than 16. Moreover an additional sternal fracture (SF) in those injuries occurs in about 10 % in case out of monolateral FCI and 21 % in bilateral FCI (1).…”
Section: Introductionmentioning
confidence: 99%
“…If the sternum ceases, painful instabilities as well as malformations with deformation of the anterior chest wall can result, which are to be treated accordingly, and with appropriate indication by surgical fixation (15)(16)(17). If, on the other hand, the sternum is accompanied by rib fractures, complex instabilities of the thoracic wall may develop, especially with ribs on both sides.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, two meta-analyses were published specifically looking at surgical management of flail chest [11,12]. They both found that the data pool was limited and based mainly on small retrospective studies.…”
Section: Flail Chestmentioning
confidence: 99%